THE ROLE OF MUSIC EDUCATION IN SOCIETY: PEDAGOGICAL, CULTURAL, AND SOCIAL DIMENSIONS (International journal of artificial intelligence, 2025)
Music education, beyond its artistic value, serves as a transformative force within society by fostering creativity, cultural awareness, and social cohesion. This article examines the role of music education in shaping human development, reinforcing cultural identity, and contributing to social integration in the context of global educational reforms. The study highlights the philosophical and pedagogical foundations of music education while analyzing its socio-cultural functions in diverse communities. Drawing upon contemporary scholarly perspectives, the paper argues that music education must be understood as a multidimensional phenomenon, one that not only cultivates musical skills but also promotes democratic participation, intercultural dialogue, and the ethical formation of individuals. Ultimately, music education emerges as a vital instrument for both personal growth and societal progress.